Safety and Efficacy of Neoadjuvant Chemoimmunotherapy versus Chemotherapy for Non-Small Cell Lung Cancer Undergoing Sleeve Resection - Qiu Y; Yu J; Guo Q; Xu J (Cancer Management and Research, 2024)
Yanjun Qiu, Jinjiang Yu, Quanmin Guo, Jingyan Xu Department of Cardiothoracic Surgery, The Quzhou Affiliated Hospital of Wenzhou Medical University, Quzhou City, Zhejiang Province, People’s Republic of ChinaCorrespondence: Jingyan Xu, Department of Pharmacy, The Quzhou Affiliated Hospital of Wenzhou Medical University, Quzhou People’s Hospital, No. 100 Minjiang Boulevard Kecheng District, Quzhou City, Zhejiang Province, 324000, People’s Republic of China, Email xjy32778463@163.comAbstract: The prognosis of locally advanced non-small cell lung cancer (NSCLC) remains poor despite the addition of neoadjuvant chemotherapy, as it has been shown to improve 5-year absolute benefit survival by only 5%. Recently, neoadjuvant immunotherapy with immune checkpoint inhibitors (ICIs), combined with chemotherapy has shown promise in the treatment of locally advanced NSCLC. For NSCLC invading the main bronchus, sleeve resection has become the preferred modality to avoid pneumonectomy and reserve more cardiac or pulmonary function and to reduce postoperative morbidity and mortality. However, there has been a paucity of evidence to evaluate the safety and efficacy of neoadjuvant chemoimmunotherapy on bronchial-vascular reconstruction owing to the limited number of patients treated by sleeve lobectomy. Despite promising initial results, key knowledge gaps remain, including the impact on bronchial-vascular reconstruction, biomarkers predictive of ICI response, and the potential for specific perioperative complications associated with neoadjuvant chemoimmunotherapy in the context of sleeve resection. This review summarizes the latest literature evidence on the efficacy and safety of neoadjuvant chemoimmunotherapy approaches to address the unmet needs of sleeve resection of NSCLC treatment, describes the biomarkers predictive of ICI responses, and perioperative outcomes of sleeve resection after neoadjuvant chemoimmunotherapy.Keywords: NSCLC, neoadjuvant chemotherapy, immune checkpoint inhibitors, sleeve lobectomy